Psychological characteristics associated with the incidence of sports injuries in athletes of individual sport - Berengüí-Gil, Ronsendo; Garcés de Los Fayos, Enrique J.; Hidalgo-Montesinos, María D. (Anales de Psicología / Annals of Psychology, 2013)
Sports injuries are one of the most negative consequences resulting from the practice of sports. There are many factors that may cause them, and right now there is growing interest in the psychological variables associated to their causes. The present study evaluated 84 athletes from four individual disciplines, different categories of competition and competitive level. 247 injuries were recorded during a two-year period with an average of 2.94 per athlete (1.47 per year). Statistically significant differences between the four studied sports injuries have been found. The older athletes suffered more injuries, as well as those with higher levels of performance. By administering the 16PF-5, IPED and SCAT, we find that athletes with low scores on Emotional Stability and Negative Energy Control, and high scores in Anxiety, have a higher injury rate. No injured subjects present a difference with the injured ones in their higher levels of Emotional Stability, Privateness and Openness to change, Control Coping, as well as in their lower Anxiety levels. Statistically significant correlations exist between the number of injuries and the athletes’ scores in Emotional Stability, Tension, Apprehension, Anxiety, and competitive trait anxiety.